Wordwalls Application In Teaching Writing Skill Experimental Research At Junior High school - Nikmatul Laili; Moh. Hafidz (Universitas Islam Negeri Palopo, 2025)
In the academic year 2024–2025, this study intends to examine how the Wordwall program affects the writing abilities of eighth-grade students at SMP Junior High School. Writing is often a challenging skill for students, particularly at the junior high school level, where issues such as limited vocabulary, grammatical errors, and lack of motivation are common. Wordwall, an educational tool designed to enhance learning through interactive exercises, was used as the medium in this study. The study used a one-group pre-test-post-test design and a quantitative pre-experimental methodology. The sample consisted of 38 students from class VIII-B. The pre-test measured students' initial writing abilities, followed by a treatment using Wordwall that focused on vocabulary enhancement, writing strategies, and real-time feedback. A post-test was carried out following the procedure to assess improvements in writing skills. Statistical analysis using a one-sample t-test showed a notable enhancement in pupils' writing skills, with the post-test scores (mean = 73.39) being higher than the pre-test scores (mean = 54.44). The results indicated the pupils' writing abilities were enhanced by using Wordwall, especially in vocabulary acquisition, idea generation, and writing organization. The findings suggest that Wordwall is an effective tool for improving junior high school pupils' writing abilities, offering an enjoyable and engaging approach to learning. The study concludes that Wordwall can be an influential resource in improving writing competencies in the digital era.